2011
DOI: 10.1016/j.trstmh.2011.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic infection of visceral leishmaniasis in hyperendemic areas of Vaishali district, Bihar, India: a challenge to kala-azar elimination programmes

Abstract: A cohort of 91 asymptomatic individuals with visceral leishmaniasis (VL) were identified during base line screening using recombinant 39-aminoacid antigen (rk-39) and polymerase chain reaction (PCR) conducted from December 2005 to June 2006 involving 997 individuals of two highly endemic villages of Vaishali district, Bihar. The point prevalence of asymptomatic infection was 98 per 1000 persons at baseline. There was no statistically significant difference between rk-39 and PCR positivity rate (P>0.05), even t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 22 publications
3
58
2
1
Order By: Relevance
“…PCR -based methods for detecting parasites are highly sensitive and have the added advantage that they may be performed on dry specimens without the need for cold-storage [22,23]. In order to optimize our accomplishments from the current cohort studies, we experimented with primers for ITS1 and 7SL RNA gene [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…PCR -based methods for detecting parasites are highly sensitive and have the added advantage that they may be performed on dry specimens without the need for cold-storage [22,23]. In order to optimize our accomplishments from the current cohort studies, we experimented with primers for ITS1 and 7SL RNA gene [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Das et al 21 out of 91 polymerase chain reaction (PCR) and/or recombinant K39 (rK39) positive but asymptomatic individuals (23.1%) progressed to clinical VL over a follow-up period of one year [14]. Singh et al reported 38 VL cases among 55 asymptomatic seropositive subjects followed up for one year (69%) [15].…”
Section: Introductionmentioning
confidence: 99%
“…The strategy needs a paradigm shift from preventing disease to preventing infection and interrupting transmission. The infectiousness of asymptomatic individuals infected with Leishmania , markers for progression to VL disease, the role of domestic animals in transmission, and the potential of PKDL as a reservoir for infection need to be better understood [92, 125127]. The implications of HIV coinfection with VL for treatment failure and relapse, transmission dynamics, and development of parasite resistance to drugs need to be studied further, and strategies need to be developed and tested as appropriate [42].…”
Section: Discussionmentioning
confidence: 99%